Market Basket Analysis For Procurement Of Food Stock Using Apriori Algorithm And Economic Order Quantity - Indradewi Adnyana, Made Sri; Hartati, Rukmi Sari; Sudarma, Made (International Journal of Engineering and Emerging Technology, 2020)
In a company, it's important to think about inventory patterns. Because without inventory management, companies can suffer losses. Perceived losses if the goods owned in the company's stock are lacking but the interest in goods is very high can cause consumers to switch to other companies and will reconsider making transactions. This also happens if the goods available in the warehouse have a large amount but the consumer's interest in the goods will experience a slight loss especially if the item has an active period so there is a buildup or loss. Therefore an item management strategy is needed. One company that can use both of these methods is Starbucks Legian. Because using the Economy Order Quality method can determine the number of subsequent orders and using a priori algorithm can help companies determine the items that need to be held more and can be given as promos with other products sold or given discounts. Using these two methods will attract consumers to shop at Starbucks Legian.